La racionalidad y el carácter científico de la dogmática jurídica - Quezada Blanco, Derby Mirko (2010)
It´s necessary to submit an abstract for academic motivation for which has developed this thesis entitled: "The rationality and the scientific character of legal doctrine." The main motivation of the dissertation is to answer the question: Is legal doctrine a science? Or, in terms of scholar Ramírez Andrés Bernasconi, under what definition is the study of law a science? The answer to this question presents considerable complexity because they often mix two disciplines: 1) a conceptual thesis, which aims to provide a definition of law to a scientific approach, and 2) a methodological thesis, with which not only aware of what they do, therefore, what lawyers should do for accommodate a particular model of science. These two aspects (conception of law and legal science model) are often conceived as a duality, so that there is a relationship of interdependence that concrete that sometimes the definition of law and legal science are the service of a particular notion of science. Sometimes defends a notion of law objectualist character (which is presented as a perfectly defined or object, using the terminology Kelsen, equipped with an objective sense), emerging as well, the notion of a science objectivist legal basis on which law is usually identified with the objectivity and value neutrality. Thus, the subject of further research lies primarily in what it means to conceive of legal dogmatic epistemological and functional, and present a summary of some ideas to illustrate how the epistemology (legal) has been relaxed considerably so that the income in science has become less demanding in this branch of knowledge.